Propuesta de diseño de un sistema de tratamiento de agua residual, para la gestión del estiércol bovino generado en el establo, en la sede Usme de la Universidad Antonio Nariño. (2024)
To carry out an optimal management and proper administration of bovine wastewater generated in the stable area of the Usme campus of the Antonio Nariño University was a challenge and pending obligation that the institution had regarding the issue of wastewater discharges without prior treatment. In this research project, a focus is placed on the design proposal for a wastewater treatment system (STAR), to solve the problem presented.